The Moral Values in Shouko Komi and Tadano Hitohito in the Anime Komi San Wa Komyushou Desu by Tomohito Oda (Sociological Study of Literature) - Sabrina Rahmanita; Tia Ristiawati; Nur Saadah Fitri Asih (Mezurashii: Journal of Japanese Studies, 2026)
This research was conducted to find out about the characterization and some morals such as aspects of moral education in the two main characters in the anime Komi San wa Komyushou desu. This anime provides an overview of some of the moral education applied in the Japanese education system and is scientifically examined using the theory put forward by Noboru. The four aspects of moral education consist of recognizing oneself, relationships with other humans, relationships with nature and noble things, relationships with social groups. The data collection technique used in this analysis is literature study technique and observation notes which are then reviewed using descriptive analysis method. The data source used in this research is the anime Komi San wa Komyushou desu with a total of 12 episodes. The results of this study found 55 data which includes characterization data and moral education theory according to Noboru. In the characterization, there are 19 data that show the various characteristics of the characters Shouko Komi and Tadano HitoHito. In the four aspects of moral education, there are 20 data owned by the character Shouko Komi and 16 data owned by the character Tadano HitoHito. Keywords: Anime Komi San wa Komyushou desu, moral education, sociology of literature, Noboru